A Dimeric 2, 9‐Diamino‐1, 10‐phenanthroline Derivative Improves Alternative Splicing in Myotonic Dystrophy Type 1 Cell and Mouse Models. Issue 68 (9th November 2018) - Li, Jinxing; Nakamori, Masayuki; Matsumoto, Jun; Murata, Asako; Dohno, Chikara; Kiliszek, Agnieszka; Taylor, Katarzyna; Sobczak, Krzysztof; Nakatani, Kazuhiko
Abstract: Expanded r(CUG) repeats are the cause of the neurological disorder myotonic dystrophy type 1 (DM1). The pathological features of DM1 include the formation of ribonuclear foci containing expanded r(CUG) repeats, which sequester the MBNL1 protein and lead to the misregulation of alternative pre‐mRNA splicing. Small molecules that bind to the r(CUG) repeats and improve alternative splicing have therapeutic potential in the treatment of DM1. Herein, the synthesis ofDDAP (a dimeric form of the CUG‐binding moleculeDAP reported previously), its binding properties to r(CUG) repeats, and its effect on the misregulation of splicing are reported. The surface plasmon resonance assay, circular dichroism spectra, and ESI‐TOF mass spectrometry results confirmed the binding ofDDAP to r(CUG)9 repeats. Studies on a DM1 cell model and a DM1 mouse model revealed thatDDAP was partially effective in the recovery of the pre‐mRNA splicing defects. The mechanism underlying this recovery was studied in vitro through a competitive binding assay, and suggested thatDDAP could interfere with the binding of MBNL1 to r(CUG) repeats in a concentration‐dependent manner. Abstract : Recovery from defects : A dimeric molecule of a 2, 9‐diaminoalkyl‐substituted 1, 10‐phenanthroline derivative (DDAP ) bound to r(CUG) n repeats is partially effective in the recovery of Clcn1 and Atp2a1 pre‐mRNAs splicing defects in vitro and in vivo (see figure). Small molecules that bind to the r(CUG) repeats and improve alternative splicing have therapeutic potential in the treatment of the neurological disorder myotonic dystrophy type 1.